2006
DOI: 10.1007/s00259-006-0237-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation and application of the sentinel lymph node concept in malignant vulvar tumours

Abstract: SLN identification permits the accurate pathological study of regional nodes and could reduce the high morbidity of current surgical treatment in vulvar tumour patients if the technique were to be adopted on a routine clinical basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 21 publications
2
35
0
1
Order By: Relevance
“…In such cases, only the sensitivity and specificity results can be given for the combination of tests used rather than only blue dye or 99m Tc separately or only both used together in all patients. However, for the other 20 studies, 50,51,[53][54][55][56][57][58][59][60][61][63][64][65][68][69][70][71][72][73][74] detection rates per groin can be given for each test separately and both tests combined (see Table 7). It is noticeable that the histopathological techniques used for the full IFL specimens were either not given or were less detailed than those used for the SLNs.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…In such cases, only the sensitivity and specificity results can be given for the combination of tests used rather than only blue dye or 99m Tc separately or only both used together in all patients. However, for the other 20 studies, 50,51,[53][54][55][56][57][58][59][60][61][63][64][65][68][69][70][71][72][73][74] detection rates per groin can be given for each test separately and both tests combined (see Table 7). It is noticeable that the histopathological techniques used for the full IFL specimens were either not given or were less detailed than those used for the SLNs.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Since the tumor is suitable for injection with a vital blue dye and/or technetium 99m and the lymphatic flow pathway is predictable, vulvar cancer is also a good target for SLN biopsy (4). Since 1994, a great number of clinical trials have been published on SLN detection and accuracy in vulvar cancer (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). In these clinical trials, the accuracy of SLN biopsy using a radiocolloid alone or in combination with a blue dye was demonstrated with a high negative predictive value (95%), but false positive cases were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have reported the use of a combination of technetium and blue dye for the SLNB procedure in vulvar CA [25,[32][33][34][35][36][37][38][39][40][41][42]. Rationale behind this practice relates to the importance of identifying the SLNs intra operatively.…”
Section: Slnb Techniquementioning
confidence: 99%